The Influence of Leaders' Self-Deprecating and Aggressive Humor on Employee's Innovative Work Behavior - Diastari, Prima; Parahyanti, Endang (Indigenous, 2023)
Abstract. Encouraging innovation is one of the keys for leaders to continue to bring the organization to compete in the industrial world. In general, leaders humor can promote innovative behavior of employees. However, the impact of negative humor, such as Self-deprecating humor and Aggressive Humor, on employee innovative work behavior is not widely known. Therefore, this study will measure the impact of the leader’s self-deprecating humor and aggressive humor on employees’ innovative work behavior. This study involved a total of 385 respondents who were recruited online using a convenience sampling technique. Respondents have characteristics that have worked or are currently working in an organization for at least 1 year, aged 19-48 years, and when working had a leader. Using the latest experimental method, namely Experimental Vignette Methodology (EVM), this study was structured with a 2x2 factorial design, within subject, which means that each respondent will receive 4 stimuli that have been designed by the researcher. All respondents received several stimulus sets in the form of narratives containing statements from the leadership, then filled out innovative work behavior surveys via the google form. Data were analyzed using factorial ANOVA repeated measure technique. The results of this study indicate that the leader self-deprecating humor and aggressive humor have a significant effect on employees’ innovative work behavior. Furthermore, there is a significant interaction effect between leader self-deprecating humor and aggressive humor on innovative work behavior of employees. This finding can be a reference for leaders to use humor as a strategy for encouraging employee innovation.Keywords: Leader humor; innovative work behavior; self-deprecating humor; aggressive humor; experimental vignette methodology